-2y+6-3y=54y-5y+13

Simple and best practice solution for -2y+6-3y=54y-5y+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2y+6-3y=54y-5y+13 equation:


Simplifying
-2y + 6 + -3y = 54y + -5y + 13

Reorder the terms:
6 + -2y + -3y = 54y + -5y + 13

Combine like terms: -2y + -3y = -5y
6 + -5y = 54y + -5y + 13

Reorder the terms:
6 + -5y = 13 + 54y + -5y

Combine like terms: 54y + -5y = 49y
6 + -5y = 13 + 49y

Solving
6 + -5y = 13 + 49y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-49y' to each side of the equation.
6 + -5y + -49y = 13 + 49y + -49y

Combine like terms: -5y + -49y = -54y
6 + -54y = 13 + 49y + -49y

Combine like terms: 49y + -49y = 0
6 + -54y = 13 + 0
6 + -54y = 13

Add '-6' to each side of the equation.
6 + -6 + -54y = 13 + -6

Combine like terms: 6 + -6 = 0
0 + -54y = 13 + -6
-54y = 13 + -6

Combine like terms: 13 + -6 = 7
-54y = 7

Divide each side by '-54'.
y = -0.1296296296

Simplifying
y = -0.1296296296

See similar equations:

| 20v=2280 | | 6(x-3)=4(3x+4) | | 259/60=37/10n | | 6x^2(4x^3y)= | | -64x^2+216=0 | | (10x-5)/(6x-9)= | | 39=42/5n | | 10x-5/6x-9= | | 3x+19+x+20=90 | | y=40-y/4 | | 5/7b=125 | | 42+5y=27 | | 12x+39x-18x=256-60x-657x | | X/5-12=9-x/3 | | 6z-12=-14+7z | | 231=7/13n | | -0.028x^2+4.578x=170 | | 2x^3-11x^2+4x+5= | | -0.028x^2+4.578x-170=0 | | 6y+3(y-2)=(3y+1)-2 | | 6x-18=12x+16 | | (1-2)(1+2)= | | 6x-18=12x | | 3x(x+2)=x-18 | | 14m*m+17m-22=0 | | (-1)(1)= | | 3/17=1/2n | | 3/17=1/2, | | y-4y-12y=0 | | Y=25-5/3x | | -1.95=.33r+.4r | | 1/2x^2-1=15 |

Equations solver categories